An Islamic Party in Urban Local Politics: The PKS Candidacy at the 2012 Jakarta Gubernatorial Election - Hidayat, Syahrul (UI Scholars Hub, 2016)
Despite its success in obtaining more votes in the 2004 general election in Jakarta than the previous election in 1999, the Partai Keadilan Sejahtera (PKS) has turn its voter sup¬port into local executive power by winning a gubernatorial election in the capital. After a narrow defeat in the 2007 local election, the party’s candidate who had a respectable reputation also failed to further its bid for the second round of the following local elec¬tion. By applying the existing possible explanations of urban candidacy in local elec¬tions, this paper aims at discussing the possible explanations for the failure of Hidayat Nur Wahid, the PKS candidate, in the 2012 gubernatorial election. The paper argues that in spite of the likely influence of religion, in this case, Islam, the party’s candidate is at the forefront position to maximise it since such other factors as personal character, to offer a candidate with the capacity to tackle urban problems makes urban voters unlikely to be on their side, although they share the similar religious identity. political resources and media are playing role in this context. In this case, the failure.